Elemental and Isotopic Signatures of Bulk Sedimentary Organic Matter in Shenhu Area, Northern South China Sea - Li, Yuanyuan; Xu, Xuemin; Pang, Lei; Guan, Ping; Fang, Yunxin; Lu, Hailong; Ye, Jianliang; Xie, Wenwei (Frontiers in Earth Science, 2022)
Hydrate-bearing sediments provide excellent materials for studying the primary sources and diagenetic alterations of the organic matter. In this study, the elemental and isotopic signatures of total organic carbon (TOC), total inorganic carbon (TIC), total nitrogen (TN) and total sulfur (TS) are systematically investigated in three hydrate-bearing sediment cores (~240m) retrieved from Shenhu area, South China Sea. All sediment layers from three sites are with low TOC content (average 0.35%) with marine and terrestrial mixed sources (-23.6‰ < δ13Corg < -21.4‰). However, the generally low δ15N (2.49–5.31‰) and C/N ratios (4.35–8.2) and their variation with depth cannot be explained by the terrestrial sources (Pearl River) and marine sources two end-member mixing processes. Contribution from lateral allochthonous organic matter from the mountainous river is considered after excluding other possible factors and ingeniously elucidating the organic matter origins. Further, specific layers in W01B and W02B exhibit elevated S/C (up to 2.39), positive bias of δ34S-TS (up to +29.7‰) and negative excursion of δ13C-TIC (up to -8.29‰), which are the characteristics of sustained occurrence of sulfate-driven anaerobic oxidation of methane. The occurrence of coupled carbon-sulfur anomaly may be accompanied by deep hydrocarbon leakage and the formation of hydrate with high saturation.